Surgical removal of bone tumour from the jaws to prepare the jaws to receive full dental compensation: Case report - Issa Saad; Mohamad Salem Rkab; Ahmad Al Manadili; Tala Alkhori; Remon Alhaja; Rama Kabani; Joudi Albokaii; Marwan Al-Raeei; Chadi Azmeh; Thayer Marouf (Elsevier, 2023)
Large bone tumors that form in the bones of the upper and lower jaws in the mouth are among the diseases associated with dental and jaw lesions. These bony tumors forming in the jaws are an obstacle to performing dental prosthetics in the jaws, whether they are dental prosthetics or restorative ones. In this case report, we present a case of surgery on the jaws of a forty-year-old Syrian young man with the aim of removing a number of bone tumors formed in the jaw bones. The dental clinic at the International University of Science and Technology performed this surgery after it became clear that it was impossible to perform dental prosthetics in the jaws due to the presence of these bone tumors in both the upper and lower jaws. The surgical operation was performed successfully, and the tumorous lesions removed from the young man's upper and lower jaws were examined, and the jaws were prepared for full dental restorations afterwards.